Identifying Pedagogical Factors Influencing the Use of Diagnostic Assessment in Secondary Classrooms - Soroushnia, Leila; Jalilian, Kamran (Assessment and Practice in Educational Sciences, 2023)
This study aimed to identify and explore the pedagogical factors influencing the implementation of diagnostic assessment in secondary classrooms. This research employed a qualitative design grounded in the interpretivist paradigm to gain a contextual understanding of teacher perceptions and practices related to diagnostic assessment. Data were collected through semi-structured interviews with 20 secondary school teachers in Tehran, selected via purposive sampling to ensure relevant experience and diversity across disciplines. The interviews were transcribed verbatim and analyzed thematically using NVivo software. Thematic saturation was reached through iterative coding and constant comparison. The analysis involved open, axial, and selective coding to identify core themes and underlying patterns across the dataset. The thematic analysis revealed four main categories shaping teachers’ use of diagnostic assessment: (1) teacher knowledge and beliefs, (2) institutional support and constraints, (3) student-related factors, and (4) pedagogical practices and classroom dynamics. Key barriers included conceptual misunderstandings about diagnostic assessment, lack of targeted professional development, time constraints, and misalignment between assessment goals and administrative priorities. Facilitators included reflective teaching habits, collaborative school culture, and instructional flexibility. Teachers emphasized the importance of student feedback literacy and the need for emotionally supportive environments for diagnostic strategies to be effective. The integration of diagnostic data into instructional planning was observed only when teachers demonstrated strong assessment literacy and institutional autonomy. Diagnostic assessment in secondary classrooms remains underutilized due to a combination of cognitive, institutional, and contextual barriers. Enhancing its application requires systemic alignment, improved teacher training, and supportive pedagogical cultures that value assessment as a formative and adaptive process.